ANALISIS PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI - Tombang Simatupang (Jurnal Ilmiah Econosains, 2013)
Abstract This paper analyses the influence of leadership and communication on employee’s performance. Employing inferential statistics, this research finds that leadership and communication are among key success factors for improving organization performance, and thus service to public. This research focuses on one public organizational within the Directorate General of Treasury, Ministry of Finance. Given similar contexts facing other public organizations, it is expected that the findings shed light on issues such as organizational performance through enhancing leadership skill and communication. Keywords: Performance, Leadership, Communication